Small-Scale Farming and Food Security: The Enabling Role of Cash Transfers in South Africa's Former Homelands - Dieter von Fintel; Louw Pienaar (Institute for the Study of Labor (IZA), 2016)
Cash transfers successfully alleviate poverty in many developing countries. South Africa is a case in point, implementing one of the largest unconditional cash transfer programmes internationally, and with substantial benefits to household well-being along multiple dimensions. Yet, grants discourage formal labour market attachment, creating dependencies on the fiscus. This study uses a fuzzy regression discontinuity design to establish that state-funded Old Age Pensions encourage non-market economic activity (in the form of small-scale farming), and improve the self-reported food security of rural households that farm, vis-à-vis those that do not. However, only non-farming households increase market food expenditure and consume more diverse diets from market-sourced foods: diet quality improves with greater spending, while food sufficiency remains unaffected. Farmers, on the other hand, do not change food spending patterns, but self-rated food sufficiency improves due to greater levels and diversity in home production. The role of small-scale farming is of broader interest in rural development, given the context of the 1913 and 1936 Land Acts that constrained this form of livelihood in former apartheid homelands. This paper's contribution is two-fold: grants are an effective channel to actively promote rural development through small-scale farming, and they improve food security by non-market mechanisms.
Keywords: Q12; Q18; Q15; D13; C26; 330; cash transfers; small-scale farming; food security; South Africa; Apartheid homelands; regression discontinuity design